STUDI ESTETIKA ARSITEKTUR LANSKAP (Studi Kasus : Danau Archipelago di Taman Mini Indonesia Indah ) - Farhan Fadila; Zefri (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2022)
Taman Mini Indonesia Indah is a famous tourist destination in DKI Jakarta. However, in 2022, TMII begins a revitalization in order to restore its dignity as a Green Open Space (RTH) and also has another goal, namely to restore the spirit of the Indonesian nation. Many buildings or places have undergone changes, especially on Archipelago Lake or a lake with miniature Indonesian islands. Archipelago Lake is used as an object of research by focusing on the aesthetics, elements, elements, principles of its landscape architectural design. The research uses a qualitative descriptive method by conducting direct research into the field and data collection research then the researcher will analyze the implementation of the aesthetics, elements, elements and principles of landscape architectural design at Archipelago Lake in the Taman Mini Indonesia Indah area, DKI Jakarta. The results of the discussion and research show that the application of landscape architecture in the Archipelago Lake area is implemented in the concept of integrated landscape and spatial planning